A hybrid analytical-numerical model for predicting the performance of the Horizontal Ground Heat Exchangers. (May 2022) - Bahmani, Mohammad Hossein; Hakkaki-Fard, Ali
Highlights: A novel hybrid analytical-numerical model for predicting the performance of HGHEs is proposed. This model can predict the long-term transient performance of linear HGHEs with various pipe arrangements. This method is based on Duhamel's theorem, modified infinite line source model, and superposition principle. The suggested model is much easier to code than CFD approaches, and its calculation time is considerably less. Abstract: Horizontal Ground Heat Exchangers (HGHE) as a means of exploiting geothermal energy has come to the fore for a few decades. Various analytical and Computational Fluid Dynamics (CFD) methods have been proposed to predict the performance of the HGHEs. The available analytical approaches are fast; however, they are based on various simplifications and assumptions, affecting their accuracy. On the other hand, CFD methods are more accurate, but their computational cost is a burden. Therefore there is an acute need for an accurate and fast method for predicting the long-term performance of HGHEs. To this aim, this study puts forward a novel hybrid analytical-numerical model for predicting the performance of HGHEs. The proposed approach is based on Duhamel's theorem, modified infinite line source method, and superposition principles that allow fast and straightforward simulation. The thermal interference between adjacent pipes is also considered via the superposition method. The computational time and performance of the proposed approach are evaluated via several benchmark cases and are compared with the results of a three-dimensional CFD model. The results depicted that the present model can predict well the transient performance of linear HGHEs with various pipe arrangements. Moreover, according to the obtained results, the proposed semi-analytical method is up to 50 times faster than the CFD approach.